The Cave 4 Apocryphon of Jeremiah and the Qumran Jeremianic Traditions: Prophetic Persona and the Construction of Community Identity - Davis, Kipp (Studies on the Texts of the Desert of Judah, 2014)
A careful reconsideration of the Apocryphon of Jeremiah C from Qumran and the Jeremianic traditions in the Qumran literature reveals the importance of Jeremiah's prophetic persona for the construction of community identity in periods of crisis